PENGARUH UKURAN PERUSAHAAN, RETURN ON ASSETS (ROA) DAN PERTUMBUHAN PENJUALAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN LQ45 YANG TERDAFTAR DI BEI PERIODETAHUN 2017-2020 - SIAHAAN, WINDA CHRISTY; Malau , Melinda; Sembiring, Caroline F. (Universitas Kristen Indonesia, 2022)
The research objective is to examine the effect of firm size on tax avoidance, the effect of Return On Assets on tax avoidance, the effect of sales growth on tax avoidance. Data analysis was carried out using descriptive analysis method, data collection method used was the documentation method. The data used is secondary data from 2017-2020. The results of this study are the variable company size is negative on tax avoidance. which means that the larger a company is, the lower the occurrence of tax avoidance, the ROA variable has no effect on tax avoidance. Low or high value of ROA has no effect on tax avoidance, sales growth variable has a negative effect on tax avoidance, which means that the higher the value of sales growth, the lower the occurrence of tax avoidance. As for the suggestions to overcome the limitations in this study, the researchers provide several research recommendations, namely that further research is suggested to increase the number of independent variables, so that research results can be more accurate.Keywords: Company Growth, Firm Size, Return on Asset, Tax Avoidance